Estudo da eletro-oxidação de moléculas orgânicas pequenas sobre multicamadas metálicas Ptpc/Rh/Pt e Ptpc/Ru/Pt utilizando FTIR in situ - Silva, Camila Daiane Ferreira da (Universidade Federal de São Carlos, 2018)
The modification of platinum-based electrodes for the efficiency optimization of the fuel cells has generated a great scientific interest, due to the problems associated with the poisoning of the catalytic surface. In addition, the use of renewable fuels is an important advantage for these systems by associating the high performance of the electric motors with the low emission of pollutants. In this way, the scientific community has studied numerous materials such as alloys and multilayer metallic structures (MM), and fuels as small organic molecules. In this work, Ptpc/M/Pt metallic multilayers were developed, in which rhodium or ruthenium was used as an intermediate layer, and their catalytic activities were investigated for the methanol and ethanol electro-oxidation in acid medium. For this purpose, cyclic voltammetry (VC) and in situ infrared spectroscopy (in situ FTIR) were used. In addition, the behavior and catalytic activity of MM Ptpc/Rh/Pt for the methanol electro-oxidation in alkaline medium using VC was evaluated. In acid medium, the compositions Ptpc/Rh2,0/Pt1,0 and Ptpc/Ru5,0/Pt2,0 presented increases of 283% and 422%, respectively, in the peak current density compared to Ptpc for the methanol oxidation and 32% and 67%, respectively, for the ethanol electro-oxidation. Using FTIR in situ, the appearance of a band at ~ 2340 cm-1, attributed to CO2, which is the total oxidation product of the alcohols, was observed. In alkaline medium, Ptpc/Rh2,0/Pt1,0 had an increase in the current density of 70% compared to Ptpc. Therefore, the addition of rhodium and ruthenium as intermediate layers promoted an improvement in the catalytic activity compared to Ptpc, probably by altering the electronic configuration of the platinum or improving the bifunctional effect.
Study of the electro-oxidation of small organic molecules on metallic multilayers Ptpc/Rh/Pt and Ptpc/Ru/Pt by FTIR in situ
Keywords: Eletrocatálise; Multicamadas metálicas; FTIR in situ; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA